Using the Delphi Technique to Achieve Consensus: A Tool for Guiding Extension Programs - Laura A. Warner (EDIS)
The ability to achieve a group consensus may be critical during specific activities throughout an Extension professional’s career. For example, it may be important to identify an advisory committee’s highest priorities or a group of stakeholders’ most important programmatic needs. The Delphi method has been recognized as a suitable alternative to interviews and formal meetings in certain circumstances. This 6-page fact sheet provides an overview of the Delphi method and suggestions for using this technique to support Extension programming. Written by Laura A. Warner and published by the UF Department of Agricultural Education and Communication, October 2014.